If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3i = -3 + 2yi Reorder the terms: 3i + x = -3 + 2yi Solving 3i + x = -3 + 2iy Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2iy' to each side of the equation. 3i + -2iy + x = -3 + 2iy + -2iy Combine like terms: 2iy + -2iy = 0 3i + -2iy + x = -3 + 0 3i + -2iy + x = -3 Add '-1x' to each side of the equation. 3i + -2iy + x + -1x = -3 + -1x Combine like terms: x + -1x = 0 3i + -2iy + 0 = -3 + -1x 3i + -2iy = -3 + -1x Reorder the terms: 3 + 3i + -2iy + x = -3 + -1x + 3 + x Reorder the terms: 3 + 3i + -2iy + x = -3 + 3 + -1x + x Combine like terms: -3 + 3 = 0 3 + 3i + -2iy + x = 0 + -1x + x 3 + 3i + -2iy + x = -1x + x Combine like terms: -1x + x = 0 3 + 3i + -2iy + x = 0 The solution to this equation could not be determined.
| X^2y^2-4= | | 3x+22=34 | | X^2+20x+51= | | n-8=-5 | | 6(p-5)= | | 5x-70=60 | | X^2+29x+100= | | (X+3)(4x+3)=13 | | p+14=12 | | y^2+10y=24 | | 34x+34=12 | | X^2+27x+50= | | 12*4/(146/2)= | | x^2+27x+100= | | 2t+4=2 | | 13+m=10 | | 6x^2-15x+5=12x+5 | | 5(y-2)-8y=-34 | | 3-5b=-32 | | x^2+19x+34= | | x^2-3x-19=7x+5 | | x^2+17x+70= | | x^2-3x-9=9 | | n-425=9 | | 7=3(x+1)-2 | | t-198=0 | | 3+x=-4 | | 3x-2(x+3)=12 | | -4(a-2)=-20 | | t-76=0 | | -9x+8i=54 | | -9x+8i=-54+(16y)i |